2017
DOI: 10.2147/rru.s118966
|View full text |Cite
|
Sign up to set email alerts
|

Microtubule-associated protein tau is associated with the resistance to docetaxel in prostate cancer cell lines

Abstract: Tau, a microtubule-associated protein, has been investigated primarily in neurons. Recently, tau has been explored to be associated with increased drug resistance in various kinds of cancers. We found that the tau was expressed in prostate cancer cell lines DU145 and PC-3. We also reported that recurrent prostate cancer cells after docetaxel treatment have higher levels of microtubule-associated protein tau. In vitro, inactivation of tau by gene knockdown suppressed cell proliferation and sensitized docetaxel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 19 publications
1
27
0
Order By: Relevance
“…The obtained results are in concordance with previous studies. For example, we observed that Microtubule-Associated Proteins (MAPs) were significant for Docetaxel and Paclitaxel in the studied cancers which aligns with previous research on this family of proteins (Yang et al, 2017;Smoter et al, 2011;Bhat and Setaluri, 2007). For Bortezomib, we observed significant associations for different proteasome subunits such as subunit alpha (PSMA) and beta (PSMB).…”
Section: Aitl Predictions For Tcga Patients Have Significant Associatsupporting
confidence: 89%
See 1 more Smart Citation
“…The obtained results are in concordance with previous studies. For example, we observed that Microtubule-Associated Proteins (MAPs) were significant for Docetaxel and Paclitaxel in the studied cancers which aligns with previous research on this family of proteins (Yang et al, 2017;Smoter et al, 2011;Bhat and Setaluri, 2007). For Bortezomib, we observed significant associations for different proteasome subunits such as subunit alpha (PSMA) and beta (PSMB).…”
Section: Aitl Predictions For Tcga Patients Have Significant Associatsupporting
confidence: 89%
“…Since the majority of the studied baselines cannot use the continuous IC50 values in the source domain, binarized IC50 labels provided by (Iorio et al, 2016) using the Waterfall approach (Barretina et al, 2012) were used to train them. Finally, for the minimax optimization, a gradient reversal layer was employed by AITL and the adversarial baselines (Ganin et al, 2016) which is a well-established approach in domain adaptation (Zhang et al, 2019;Long et al, 2018;You et al, 2019). We performed 3-fold cross validation in the experiments to tune the hyper-parameters of AITL and the baselines based on the AUROC.…”
Section: Does Aitl Outperform a Baseline For Inductive Transfer Learnmentioning
confidence: 99%
“…However, many patients show continued resistance to taxane-based chemotherapy. Multiple molecular players are linked to taxane resistance; these include efflux pumps (10), DNA repair mechanisms (11), and microtubule alterations (12). In addition, emerging evidence indicates that both non-coding RNAs and epigenetic effectors may also be implicated in taxane resistance (7).…”
Section: Introductionmentioning
confidence: 99%
“…This stabilizes microtubules and influences transportation of cellular secretory proteins. Moreover, MAPT has been reported to accelerate cancer cell growth [ 119 ], while its inactivation through gene knockdown suppressed cell proliferation [ 120 ]. Therefore, it is speculated that the diverse affinity of a natural drug to different functional protein targets may be one of the key factors for different selectivity profiles on VSMCs or VECs.…”
Section: Selective Inhibition Of Vsmcs Versus Vecs Shows Significamentioning
confidence: 99%